1991
DOI: 10.1113/jphysiol.1991.sp018724
|View full text |Cite
|
Sign up to set email alerts
|

Cell volume regulation by trout erythrocytes: characteristics of the transport systems activated by hypotonic swelling.

Abstract: SUMMARY1. An osmolality reduction of the suspending medium leads to osmotic swelling of trout erythrocytes, which is followed by a volume readjustment towards the original level. The regulatory volume decrease (RVD) was not complete after 1 h.2. During RVD the cells lost K+ and Cl-but gained Nat. This entry of Na+, which is about half the K+ loss, explains the incomplete volume recovery (it was complete when Na+ was replaced by impermeant N-methyl-D-glucamine). The cells also lose large quantities of taurine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 32 publications
3
63
2
Order By: Relevance
“…In addition, the volume-activated K+ pathway in this case is essentially Cl-independent, i.e. K+ loss is not, or only slightly, reduced by replacement of Cl-by NO3- (Garcia-Romeu, Cossins & Motais, 1991). Thus in trout erythrocytes two types of volume-dependent K+ pathways co-exist, and we have demonstrated that the cells adopt one rather than the other depending on changes of cellular ionic strength induced by swelling (Motais, Guizouarn & Garcia-Romeu, 1991).…”
Section: Introductionmentioning
confidence: 59%
“…In addition, the volume-activated K+ pathway in this case is essentially Cl-independent, i.e. K+ loss is not, or only slightly, reduced by replacement of Cl-by NO3- (Garcia-Romeu, Cossins & Motais, 1991). Thus in trout erythrocytes two types of volume-dependent K+ pathways co-exist, and we have demonstrated that the cells adopt one rather than the other depending on changes of cellular ionic strength induced by swelling (Motais, Guizouarn & Garcia-Romeu, 1991).…”
Section: Introductionmentioning
confidence: 59%
“…As shown in fish erythrocytes in particular (Garcia-Romeu et al 1991;Goldstein & Brill, 1991;Kirk et al 1992;Haynes & Goldstein, 1993), this volume-activated efflux is inhibited by inhibitors of anion exchangers (DIDS and niflumic acid), and of chloride channels (NPPB,MK 196), but not by inhibitors of Na+-K+-2Cl-cotransport (frusemide). It has been proposed that the volume-stimulated taurine efflux behaves more like a chloride channel than a saturable carrier.…”
Section: Discussionmentioning
confidence: 99%
“…This contribution has been described in invertebrates and also in mammalian tissues such as cardiac cells (Thurston, Hauhart & Naccarato, 1981), Ehrlich cells (Hoffmann & Lambert, 1983;Lambert, 1984;Lambert & Hoffmannn, 1993) (Fugelli & Thoroed, 1986;Kirk, Ellory & Young, 1992), the skate (Goldstein & Brill, 1990, the eel (Fincham, Wolowyk & Young, 1987) and the trout (Garcia-Romeu, Cossins & Motais, 1991), and also in the cyclostomes, hagfish and lamprey (Brill, Musch & Goldstein, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…By expression studies of tAE1 in Xenopus oocytes, we have demonstrated previously that this normally electroneutral anion exchanger is able to form an anion conductive path-way permeable to different charged or neutral osmolytes such as urea, choline, sorbitol, Na Ï© , and K Ï© (13)(14)(15). In physiological conditions, these transport properties of tAE1 are activated by a decrease in intracellular ionic strength in swollen erythrocytes, and they are involved in the cell regulatory volume decrease response (16,17). Here, we focused on another unexpected feature of this anion exchanger.…”
mentioning
confidence: 99%